The θ-twistor versus the supertwistor - Zheltukhin, A.A. (Вопросы атомной науки и техники, 2007)
We introduce the θ-twistor, which is a new supersymmtric generalization of the Penrose twistor and is also alternative to the supertwistor. The θ-twistor is a triple of spinors including the spinor θ extending the Penrose’s double of spinors. Using the θ-twistors yields an infinite chain of massless higher spin chiral supermultiplets (1/2,1), (1,3/2), (3/2,2),…,(S,S+1/2) generalizing the known scalar (0,1/2) supermultiplet. Вводиться θ-твистор, що є новим суперсиметричним узагальненням твістора Пенроуза, альтернативним супертвістору. θ-твістор є триплетом спінорів, що включає спінор θ, який розширює дублет спінорів Пенроуза. Використання θ-твісторів приводить до нескінченого ланцюжку безмасових кіральних супермультиплетів вищих спінів (1/2,1), (1,3/2), (3/2,2),…,(S,S+1/2), які узагальнюють відомий скалярний (0,1/2) супермультиплет. Вводится θ-твистор, являющийся новым суперсимметричным обобщением твистора Пенроуза, альтернативным супертвистору. θ-твистор является триплетом спиноров, включающим спинор θ, который расширяет дублет спиноров Пенроуза. Использование θ-твисторов приводит к бесконечной цепочке безмассовых киральных супермультиплетов высших спинов (1/2,1), (1,3/2), (3/2,2),…,(S,S+1/2), обобщающих известный скалярный (0,1/2) супермультиплет.